Characterization of Produced Novel Nanobody Against CD19 Marker - Issa, Awatif H.; Yousef, Samar K. (Scientific Journal of Medical Research, 2021)
Objectives: The engineered single domain antibodies, which produced against CD19 immune receptor, distinguished by many properties Methods: Here, a set of characteristics were described, including protein expression of VHH gene in positive transformed Er2738 colonies VHH gene expression was detected by Real-Time PCR (RT-PCR) so threshold cycle Ct was 34.9, purification of soluble nanobodies’ protein carried out in which the fractionation of the dissolved nanobodies protein from other periplasmic proteins using a gel chromatography by Sephadex LH-G20. Results: The resulting curve illustrated a unique peak with the highest optical density (OD) of 280nm was 0.58. The specificity of soluble nanobodies against CD19 at 37°C and 80°C were determined by Enzyme-Linked Immunosorbent Assay ( ELISA). Conclusion: The results demonstrated characteristics feature of nanobodies' ability to bind specifically with the interested antigen at a temperature of 37°C and continued their effectiveness at 80°C, which is the diagnostic characteristic of nanobodies.